Between Love and Affection: Rahmatan Lil Alamin as a Transformative Axiological Framework in Global Education - Mokhtar, Ahmad Baha' bin; Rahman, Mohammad Taufiq (FOCUS, 2025)
This study explores the paradigm of Rahmatan Lil Alamin as a transformative axiological framework for reorienting global education in an era marked by instrumentalism, ecological crisis, and moral disintegration. Employing a descriptive qualitative method with a philosophical and interpretive literature-based approach, the paper critically examines how Islamic values of universal compassion, justice, and ethical responsibility can enrich and redirect the purpose of education beyond utilitarian ends. The findings reveal that when Rahmatan Lil Alamin is integrated into educational thought and practice, it enables the emergence of a holistic pedagogy that cultivates not only intellectual competence but also moral sensibility, ecological awareness, and spiritual depth. This paradigm positions education as a moral and civilizational project—one that fosters the formation of ethically grounded individuals committed to the common good. Rather than treating education as a neutral mechanism for economic mobility, Rahmatan Lil Alamin recasts it as an ethical vocation rooted in values that transcend religious, cultural, and disciplinary boundaries. The study contributes to the contemporary discourse on Islamic philosophy of education by constructing an integrative, value-based, and globally relevant framework for building an impactful, compassionate, and sustainable model of higher education.